Republic of Tajikistan : Report on the Observance of Standards and Codes (ROSC)-Data Module. - International Monetary Fund. (Washington, D.C. : International Monetary Fund, 2005)
This Report of the Observance of Standards and Codes (ROSC) Data Module provides an assessment of Tajikistan's macroeconomic statistics against the recommendations of the General Data Dissemination System (GDDS), complemented by an assessment of data quality based on the IMF's Data Quality Assessment Framework. The assessment reveals that Tajikistan already meets many of the GDDS recommendations for dissemination of macroeconomic statistics. The main exceptions are the coverage of national accounts, central government operations, and central government debt. All data categories meet or exceed the recommended periodicity and timeliness.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet